생애주기별 남성 음주자의 문제음주 영향요인에 관한 연구 - 홍지연(Hong, Jiyeon); 김지현(Kim, Jihyun); 김옥수(Kim, Oksoo) (Sŏngin Kanho Hakhoe chi, 2014)
Purpose: This study was aimed to investigate the factors influencing problem drinking of male drinkers above 19 years old according to the life cycle. Methods: The study subjects consisted of a representative community sample of 2,229 male drinkers aged 19 and older from the 2011 Korean National Health and Nutrition Examination Survey. The collected data were analyzed using descriptive statistics, Rao-Scott $x^2$-test, simple and multiple logistic regressions. Results: The problem drinking rates were 38.7% in adolescence, 44.5% in middle age, and 23.9% in senescence. In adolescence, the predictors of problem drinking included occupation, stress recognition, and smoking. In middle age, the predictors of problem drinking were education level, depression, and smoking. In senescence, the predictors of problem drinking were not identified in this study. Conclusion: The findings of this study suggested that the factors influencing problem drinking of male drinkers were different according to life cycle. Thus different intervention methods should be developed for each age group in order to intervene the problem drinking.